Structural transformation and employment conditions the case of Negros Occidental Province. - Miralles, Queny Roselle M.; Miralles, Queny Roselle M. (1999.)
This paper attempts to investigate the structural tranformation and trends in employment condition of the labor force of Negros Occidental as development takes place development which is said to provide productive and satisfying activities among the populace, especially the working age population. Using four sets of data from the Labor Force Survey of the National Statistics Office, the study reveals that, during the period covered by the study (1988-1995), employment conditions in the province remained stagnant, having large portion of its labor force engaged in agricultural activities and showing no significant improvement in the industrial and service sectors. This finding suggests that during those times, there had not been significant improvement in the human condition of the impoverished majority in the province in terms of poverty reduction and improved income distribution.
Thesis (Undergraduate, Bachelor of Arts in Economics-Management) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Employment -- Negros Occidental